Anti-human TREM2 induces microglia proliferation and reduces pathology in an Alzheimer’s disease model - Wang, Shoutang; Mustafa, Meer; Yuede, Carla M.; Salazar, Santiago Viveros; Kong, Philip; Long, Hua; Ward, Michael; Siddiqui, Omer; Paul, Robert; Gilfillan, Susan; Ibrahim, Adiljan; Rhinn, Hervé; et al. (The Journal of experimental medicine, 2020)
TREM2 is a receptor for lipids expressed in microglia. The R47H variant of human TREM2 impairs ligand binding and increases Alzheimer’s disease (AD) risk. In mouse models of amyloid β (Aβ) accumulation, defective TREM2 function affects microglial response to Aβ plaques, exacerbating tissue damage, whereas TREM2 overexpression attenuates pathology. Thus, AD may benefit from TREM2 activation. Here, we examined the impact of an anti-human TREM2 agonistic mAb, AL002c, in a mouse AD model expressing either the common variant (CV) or the R47H variant of TREM2. Single-cell RNA-seq of microglia after acute systemic administration of AL002c showed induction of proliferation in both CV- and R47H-transgenic mice. Prolonged administration of AL002c reduced filamentous plaques and neurite dystrophy, impacted behavior, and tempered microglial inflammatory response. We further showed that a variant of AL002c is safe and well tolerated in a first-in-human phase I clinical trial and engages TREM2 based on cerebrospinal fluid biomarkers. We conclude that AL002 is a promising candidate for AD therapy.